Qualitative analysis of IgM antibody in tuberculosis - Ram Narayan Mandal,; Ajay Kumar Mishra,; Elena Leonidovna Mandal,; Margarita Ramovna Mandal,; Vijay Kumar Sah,; Rajiv Jha, (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Nearly one third of the global population is infected with mycobacterium tuberculosis and at risk of developing the disease. More than eight million people develop active tuberculosis every year and about two million dies. Thus, this study was evaluated to study of the sensitivity and specificity of IgM antibody by ICT (Immuno-chromatographic test) method in diagnosing tuberculosis. Materials and Methods: This study comprised of 100 subjects, of which 25 were sputum positive tuberculosis, 25 were sputum negative tuberculosis diagnosed on the basis of clinical and radiological backgrounds, and 50 subjects were taken as control of which 25 were chest infections other than tuberculosis and the rest of 25 were clinically normal subjects. Results: The sensitivity and specificity of IgM antibody was found to be 32% and 94% in the AFB positive group, where as in the AFB negative group it came out to be 24% and 94%, overall, on combining both the group the sensitivity and specificity of IgM antibody came out to be 28% and 94%. Conclusion: Serum IgM antibody test has a low sensibility in diagnosing tuberculosis, but it can be helpful in excluding tuberculosis in individuals suspected to have tuberculosis.